Pengaruh Gaya Kepemimpinan Demokratis dan Motivasi Kerja Terhadap Kinerja Pegawai Kantor Kementerian Agama Kabupaten Mamuju - Ferils, Muh; Utami, Mega (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2022)
This study aims to determine the effect of democratic leadership style and work motivation on the performance of the employees of the Ministry of Religion in Mamuju Regency. This study uses a quantitative approach, the data collection method uses a survey method through the distribution of questionnaires that are filled directly by employees at the agency. The sampling total sampling, in this study all the population was sampled with a total of 74 respondents. The data analysis technique was to test each item of the research instrument using validity and reliability tests. analysis technique Hypothesis testing using multiple linear regression analysis and Partial Test (t statistical test). The t-table value obtained from the distribution table is 1.994 and the confidence level used is 0.05. The results of multiple regression analysis in this study is a constant 2.165. The correlation coefficient of X1 is 0.568 with a t-value of7.003 and a significance of 0.000. The correlation coefficient of X2 is 0.337 with a t-value of 4.523and significance of 0.000. From these results, the writer interprets the t-value of7.003 > t-table value 1,994 with a significance level of 0.00 < 0.05. While the t value oftable work motivation (X2) is 4,523 > t1,994 with a significance value of 0.00 < 0.05. The results of the analysis of the data obtained answered the initial assumptions put forward by the researcher and it was proven true that the Democratic Leadership Style and Work Motivation had a positive and significant effect on the Performance of the Office of the Ministry of Religion in Mamuju Regency..